2018
DOI: 10.1055/s-0038-1649508
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and Large-Sized Autologous Breast Reconstruction using a Fleur-de-lys Profunda Femoris Artery Perforator Flap Design: A Report Comparing Results with the Horizontal Profunda Femoris Artery Perforator Flap

Abstract: The fleur-de-lys skin paddle design not only allows an increase of the horizontal PAP flap volume, but also increases the skin surface, with an acceptable donor site morbidity. For medium- or large-sized breasts, the fleur-de-lys PAP flap seems to be ideal when a DIEP flap-based reconstruction is contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Among the 12 studies finally identified, 516 PAP flaps were included and their characteristics are shown in Table 1 [24, 27, 3443]. They were all published in the past four years, four studies in the United States of America, three in France, three in China, and two, respectively, in the United Kingdom and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 12 studies finally identified, 516 PAP flaps were included and their characteristics are shown in Table 1 [24, 27, 3443]. They were all published in the past four years, four studies in the United States of America, three in France, three in China, and two, respectively, in the United Kingdom and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have also established the limitations of the They reported a mean horizontal diameter of 16.7 cm and a mean vertical diameter of 16.5 cm. Since this report, modified and extended versions of the PAP flap have been reported, including vertical and fleur-de-lys designs (Bourn et al, 2019;Hunsinger et al, 2019;Rivera-Serrano, Aljaaly, Wu, & Cheng, 2017). The modifications even evolved to inverted-L design to meet the demand for required breast volumes (Scaglioni, Eder, & Giovanoli, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies not relevant (142 articles), cadaver or imaging studies (7 articles), case reports (5 articles), reviews (1 article), and reports in languages other than English (3 articles) were further excluded, resulting in 18 articles for full-text review. After excluding 10 articles lacking extractable data or with suspected cohort overlap, 8 articles were included in the systematic analysis (Figure 1b)(Allen Jr et al, 2016;Ciudad et al, 2016;Haddock, Gassman, Cho, & Teotia, 2017;Hunsinger et al, 2019;Hunter et al, 2015;Hupkens et al, 2016;Satake et al, 2014;Scaglioni, Chen, Lindenblatt, & Giovanoli, 2017…”
mentioning
confidence: 99%
“…The main disadvantage of PAP flap reconstruction of the breast remains its relatively limited volume for large reconstructions, especially compared to the DIEP flap (12,29). Average DIEP flap volumes have been reported to be around 700 g, while PAP flap volumes average 220 to 405 g with the ability to expand to 480 g by modifying flap design (29)(30)(31)(32)(33). Augmenting with another flap, implant, or fat grafting represent additional potential workarounds to this drawback.…”
Section: Pap Flap: Advantages and Disadvantagesmentioning
confidence: 99%